Upaya Peningkatan Kesehatan Mental pada Siswa MAN 2 Surakarta - Annisa Siti Solikah Satriadanie; Faqih Purnomosidi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Adolescence is a transition period from childhood to adulthood marked by rapid physical, psychological, and social changes. One important aspect in adolescent development is mental health, which plays a role in forming healthy, resilient, and productive individuals. However, awareness of mental health among adolescents is still relatively low, as found in observations at MAN 2 Surakarta. Increasing awareness of mental health problems and support from family, friends, and the wider community is needed to create a healthy and productive young generation. From the author's observations at MAN 2 Surakarta, it was found that some students were not yet familiar with the concept of mental health, so this community service activity was carried out. Therefore, this community service activity was carried out to increase student awareness of the importance of mental health, provide education, and develop stress management skills. This activity involves delivering materials, discussions, and practicing relaxation techniques such as the butterfly hug. The purpose of this activity is to increase awareness of the importance of mental health, provide education about mental health, and also develop stress management skills. So that students are expected to be able to live a healthier and stronger life both mentally and emotionally. It is also hoped that students can become mentally strong individuals who also have positive behavior for themselves and their surroundings. The results of the activity showed an increase in students' understanding of mental health, with positive and enthusiastic responses from participants.